Excipients in formulations for clinical trials: Getting it right the first time - Shireesh Apte (Journal of Excipients and Food Chemicals)
An ignorant and therefore, nonchalant and indifferent attitude, bordering on the cavalier, toward excipients as potential enablers for drug delivery, creates a hubris in the early stages of the drug development process that serves to dismiss the pivotal role played by the excipients/delivery system as a contributory factor to the success of POC clinical studies. The result is an API that is poorly formulated (and hence sub-optimally bioavailable at its site of action), and unlikely to achieve statistical significance with regard to the clinical trial objectives. It is time that the Pharmaceutical community incorporated relevant excipients earlier in the drug development process to increase the probability of success in clinical trials and the return on investment, a shorter time to market and, ultimately, a greater probability to ease the suffering caused by disease.